Networked Cages for Enhanced CO2 Capture and Sensing. Issue 7 (17th May 2018) - Wang, Zhen; Ma, Hui; Zhai, Tian‐Long; Cheng, Guang; Xu, Qian; Liu, Jun‐Min; Yang, Jiakuan; Zhang, Qing‐Mei; Zhang, Qing‐Pu; Zheng, Yan‐Song; Tan, Bien; Zhang, Chun
Abstract: It remains a great challenge to design and synthesize a porous material for CO2 capture and sensing simultaneously. Herein, strategy of "cage to frameworks" is demonstrated to synthesize fluorescent porous organic polymer (pTOC) by using tetraphenylethylene‐based oxacalixarene cage (TOC) as the monomer. The networked cages (pTOC) have improved porous properties, including Brunauer–Emmett–Teller surface area and CO2 capture compared with its monomer TOC, because the polymerization overcomes the window‐to‐arene packing modes of cages and turns on their pores. Moreover, pTOC displays prominent reversible fluorescence enhancement in the presence of CO2 in different dispersion systems and fluorescence recovery for CO2 release in the presence of NH3 ·H2 O, and is thus very effective to detect and quantify the fractions of CO2 in a gaseous mixtures. Abstract : Networked cages are synthesized by covalently coupling tetraphenylethylene‐based oxacalixarene molecular cages. Overcoming the window‐to‐arene packing modes of cages to turn on their pores, the obtained cage‐based emissive polymer exhibits enhanced CO2 uptake and displays prominent reversible fluorescence enhancement in the presence of CO2 and fluorescence recovery for CO2 release.